Methicillin-Resistant Staphylococcus Aureus in orthopedic surgery: Current evidence from diagnosis until rehabilitative management - Yosia Handoko; Muhammad P. Johan; Muhammad A. Usman; Muhammad Sakti; Jainal Arifin; Rizalinda Sjahril; Andi Rofian Sultan; Yunialthy Dwia Pertiwi; Rafael Marvin Yushan; Samuel Andi Kusuma (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a significant threat in orthopaedic surgery. This study aimed to evaluate the current evidence from diagnosis to rehabilitative management of MRSA in orthopedic surgery Methods: This narrative overview synthesized current evidence across the care pathway in orthopaedics, epidemiology and pathogenesis (including key resistance/virulence determinants), diagnostic approaches (sampling strategies and rapid molecular tests), therapeutic strategies (surgery plus tailored antimicrobials and local delivery), rehabilitation considerations, prevention and stewardship programs, and emerging modalities (new antibiotics, bacteriophages, and nanotechnology-enabled delivery). Results: MRSA resistance is primarily mediated by mecA (PBP2a) and augmented by additional virulence factors (e.g., panton-valentine leukocidin). Biofilm on orthopaedic implants protects bacteria from host defences and antibiotics, underpinning recurrent infection. Diagnostic yield improves with deep tissue or implant-associated sampling, while polymerase chain reaction expedites detection of resistance genes to guide early management. Optimal treatment typically combines surgical debridement with implant retention or exchange where appropriate and prolonged, targeted antimicrobials; adjuncts include local antibiotic carriers and negative-pressure wound strategies. Innovative options—novel agents, bacteriophage therapy, and nanotechnology-based delivery—show promise in early studies. Conclusion: Integrated programs, preoperative screening/decolonization, risk-adapted prophylaxis, and antimicrobial stewardship have helped lower MRSA infection rates, yet biofilm biology and rising resistance sustain a substantial burden. Emerging options include linezolid/tedizolid or minocycline plus rifampicin, with efficacy superior to vancomycin, bacteriophage therapy as an adjunct in refractory prosthetic joint infections, and nanotechnology-enabled implant coatings to deter biofilm formation.